FcγR Binding and ADCC Activity of Human IgG Allotypes - de Taeye, Steven W.; Bentlage, Arthur E. H.; Mebius, Mirjam M.; Meesters, Joyce I.; Lissenberg-Thunnissen, Suzanne; Falck, David; Sénard, Thomas; Salehi, Nima; Wuhrer, Manfred; Schuurman, Janine; Labrijn, Aran F.; Rispens, Theo; et al. (Frontiers in Immunology, 2020)
Antibody dependent cellular cytotoxicity (ADCC) is an Fc-dependent effector function of IgG important for anti-viral immunity and anti-tumor therapies. NK-cell mediated ADCC is mainly triggered by IgG-subclasses IgG1 and IgG3 through the IgG-Fc-receptor (FcγR) IIIa. Polymorphisms in the immunoglobulin gamma heavy chain gene likely form a layer of variation in the strength of the ADCC-response, but this has never been studied in detail. We produced all 27 known IgG allotypes and assessed FcγRIIIa binding and ADCC activity. While all IgG1, IgG2 and IgG4 allotypes behaved similarly within subclass, large allotype-specific variation was found for IgG3. ADCC capacity was affected by residues 291, 292 and 296 in the CH2 domain through altered affinity or avidity for FcγRIIIa. Furthermore, allotypic variation in hinge length affected ADCC, likely through altered proximity at the immunological synapse. Thus, these functional differences between IgG allotypes have important implications for therapeutic applications and susceptibility to infectious-, allo- or auto-immune diseases.